Do Salamanders Limit the Abundance of Groundwater Invertebrates in Subterranean Habitats? - Raoul Manenti; Enrico Lunghi; Benedetta Barzaghi; Andrea Melotto; Mattia Falaschi; Gentile Francesco Ficetola (Diversity, 2020)
Several species of surface salamanders exploit underground environments; in Europe, one of the most common is the fire salamander (Salamandra salamandra). In this study, we investigated if fire salamander larvae occurring in groundwater habitats can affect the abundance of some cave-adapted species. We analyzed the data of abundance of three target taxa (genera Niphargus (Amphipoda; Niphargidae), Monolistra (Isopoda; Sphaeromatidae) and Dendrocoelum (Tricladida; Dedrocoelidae)) collected in 386 surveys performed on 117 sites (pools and distinct subterranean stream sectors), within 17 natural and 24 artificial subterranean habitats, between 2012 and 2019. Generalized linear mixed models were used to assess the relationship between target taxa abundance, fire salamander larvae occurrence, and environmental features. The presence of salamander larvae negatively affected the abundance of all the target taxa. Monolistra abundance was positively related with the distance from the cave entrance of the sites and by their surface. Our study revealed that surface salamanders may have a negative effect on the abundance of cave-adapted animals, and highlited the importance of further investigations on the diet and on the top-down effects of salamanders on the subterranean communities.